Determination of gamma-globulin at nanogram levels by its quenching effect on the fluorescence of a red emitting conjugated polymer. (2nd June 2015) - Zhang, Ping; Zhuo, Shujuan; Sun, Lilin; Zhang, Ping; Zhu, Changqing
<x xml:space="preserve">Abstract</x> A novel red emitting fluorescence sensor has been constructed and used for the selective assay of gamma-globulin in the presence of serum albumin.